Unbuilt masterworks of the 21st century : inspirational architecture for the digital age - Jones, Will. (London : Thames & Hudson, 2009)
Presents some of the most creative works from architects around the world that never came to fruition.
'100 of the best project proposed since the turn of the millennium by the world's greatest architects' - back cover.
Includes bibliographical references and index.
Keywords: Architecture, Modern -- 21st century -- Designs and plans; Architectural rendering -- Computer-aided design; Unbuilt architectural projects -- 21st century